English Capacity Building in Preparing Competent Logistics Sector’s Staff in Indonesia - Yusi Rahmawati; Suprapto Suwaji (Journal of English Education and Teaching, 2022)
Logistic sectors are moving forward day by day, year by year. Their evolution brings big changes in the economic growth of countries. It drives the significant improvement in human life includes human life style, human’s needs, and human capacity. Their services has to be in agile and effective ways to reach the customer’s satisfaction. This research observes the capacity building of human resource in logistic sector in supporting the performance development of logistic companies in Indonesia especially about English capacity. The researchers use qualitative research in logistics sectors by observing, interviewing, and disseminating questionnaire to the owner, director, manager, supervisor of logistic company. Based on the research’s result, English capacity had by operational and administration staffs of a logistic company influence the business because a staff that has good English skills will run the communication as well to the customers directly and indirectly. It is because the customers of a logistic company are international customer and foreign company which have representative office in Indonesia. Explicitly, the results show that a maritime academy should prepare the human resource or in this context is a logistic sectors’ staff candidate must understand about the use of English before working in logistic sectors to support the moving forward of the company.